Transplantation of Kidneys From Donors With Acute Kidney Injury: Friend or Foe?. Issue 2 (25th August 2016) - Boffa, C.; van de Leemkolk, F.; Curnow, E.; Homan van der Heide, J.; Gilbert, J.; Sharples, E.; Ploeg, R. J.
Abstract : The gap between supply and demand in kidney transplantation has led to increased use of marginal kidneys; however, kidneys with acute kidney injury are often declined/discarded. To determine whether this policy is justified, we analyzed outcomes of donor kidneys with acute kidney injury (AKI) in a large UK cohort. A retrospective analysis of the UK Transplant Registry evaluated deceased donors between 2003 and 2013. Donors were classified as no AKI, or AKI stage 1–3 according to Acute Kidney Injury Network (AKIN) criteria. Relationship of AKI with delayed graft function/primary nonfunction (DGF/PNF), estimated glomerular filtration rate (eGFR), and graft‐survival at 90 days and 1 year was analyzed. There were 11 219 kidneys (1869 [17%] with AKI) included. Graft failure at 1 year is greater for donors with AKI than for those without (graft survival 89% vs. 91%, p = 0.02; odds ratio (OR) 1.20 [95% confidence interval (CI): 1.03–1.41]). DGF rates increase with donor AKI stage (p < 0.005), and PNF rates are significantly higher for AKIN stage 3 kidneys (9% vs. 4%, p = 0.04) Analysis of association between AKI and recipient eGFR suggests a risk of inferior eGFR with AKI versus no AKI (p < 0.005; OR 1.25 [95% CI: 1.08–1.31]). We report a small reduction in 1‐year graft‐survival of kidneys from donors with AKI. We conclude that AKI stage 1 or 2 kidneys should be used; however, caution is advised for AKI stage 3 donors. Abstract : This analysis of the UK transplant registry investigates the use of kidneys from deceased donors with acute kidney injury and analyzes the outcomes of transplanted kidneys with injury.